Unlocking the sustainability potential of Liberica coffee (Coffea liberica) in Riau’s tropical peatlands: Strategic insights from Rangsang Island, Indonesia - Muhammad Giri Wibisono; Chay Asdak; Wawan; Sophia Dwiratna (Sustainable Futures)
Tropical peatlands in Indonesia present a promising yet challenging environment for sustainable agricultural practices, particularly through the cultivation of Liberica coffee (Coffea liberica). This study investigates the sustainability of smallholder Liberica coffee plantations on Rangsang Island, Riau Province, focusing on five critical dimensions: ecological, economic, social, technological, and institutional. The study involved 82 farmers through field surveys, interviews, and direct observations. The data were analyzed using the Multidimensional Scaling Rapid Appraisal for Sustainability (MDS-RAPS) method, supported by Monte Carlo simulations to ensure robustness. The findings reveal that the overall sustainability status falls within the ''less sustainable'' category, with a composite index of 39.42. Among the dimensions, social sustainability performed best with a score of 60.68, followed by economic (44.50), ecological (35.44), institutional (32.19), and technological (24.29) aspects. Key issues identified include limited infrastructure, weak institutional support, and ecological vulnerabilities related to peat soil characteristics. Addressing these challenges requires integrated water management, strengthening of farmer groups and microfinance access, adoption of agroforestry systems, and enhanced agricultural training. The findings emphasize the need for integrated, multidimensional strategies to strengthen the resilience of Liberica coffee farming on peatlands, offering practical pathways for policymakers, practitioners, and local communities to achieve both agricultural and environmental sustainability.